PERBANDINGAN HASIL PEMERIKSAAN KOLESTEROL TOTAL MENGGUNAKAN SAMPEL SERUM DAN PLASMA EDTA SEGERA DAN DISIMPAN SELAMA 4 JAM - Luvia Isma Hanifah; Dini Puspodewi; Ira Pangesti (Klinikal Sains : Jurnal Analis Kesehatan, 2024)
Cholesterol is a lipid substance (fat component) being one among other known components, fat being a nutrient that is fulfilled by the body. The purpose of the study was to determine the comparative results of total cholesterol examination using serum and plasma EDTA immediately and stored for 4 hours. This study is analytic using cross sectional research design. The results showed in statistical tests using the Paired Sample T-Test test on serum samples immediately examined and stored for 4 hours found (p=0.015) so that the results (p>0.05) concluded there was no difference in serum samples. EDTA plasma samples immediately examined and stored for 4 hours found the results (p<0.001), comparison of total cholesterol levels using serum and EDTA plasma samples immediately examined and stored for 4 hours found (p<0.001) so that the results (p<0.05) are concluded there is a difference between total cholesterol levels in EDTA plasma immediately examined and stored for 4 hours and serum and EDTA plasma immediately examined and stored for 4 hours. Key Words : Cholesterol, Serum, EDTA Plasma, 4 Hour Delay